2018
DOI: 10.5194/os-14-53-2018
|View full text |Cite
|
Sign up to set email alerts
|

South Atlantic meridional transports from NEMO-based simulations and reanalyses

Abstract: Abstract. The meridional heat transport (MHT) of the South Atlantic plays a key role in the global heat budget: it is the only equatorward basin-scale ocean heat transport and it sets the northward direction of the global cross-equatorial transport. Its strength and variability, however, are not well known. The South Atlantic transports are evaluated for four state-of-the-art global ocean reanalyses (ORAs) and two free-running models (FRMs) in the period 1997-2010. All products employ the Nucleus for European … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 73 publications
3
25
0
Order By: Relevance
“…This comparison shows that the reanalysis products are more accurate than the free-running models at representing the AMOC's strength and meridional heat transport at 35°S and the NBUC volume transport at 11°S. Although the heat and volume transports are systematically underestimated across models, GLORYS2V4 is the one that shows the highest agreement with observations (Mignac et al, 2018). Drijfhout et al (2003) have also found that eddy-permitting models are essential to correctly represent the Lagrangian pathways in the thermocline.…”
Section: Reanalysis Model Glorys2v4mentioning
confidence: 73%
See 2 more Smart Citations
“…This comparison shows that the reanalysis products are more accurate than the free-running models at representing the AMOC's strength and meridional heat transport at 35°S and the NBUC volume transport at 11°S. Although the heat and volume transports are systematically underestimated across models, GLORYS2V4 is the one that shows the highest agreement with observations (Mignac et al, 2018). Drijfhout et al (2003) have also found that eddy-permitting models are essential to correctly represent the Lagrangian pathways in the thermocline.…”
Section: Reanalysis Model Glorys2v4mentioning
confidence: 73%
“…Our region of study is the South Atlantic Ocean between 30°S and 5°S and down to 1,500 m. The position of the northern and southern boundaries ensures that the entire subtropical-tropical boundary is contained in the domain and further warrants that the particles circulate only once through either the subtropical or the tropical gyre before leaving the domain. Mignac et al (2018) have recently performed an exhaustive comparison between current data assimilation products (including GLORYS2V4), free-running models, and observations. This comparison shows that the reanalysis products are more accurate than the free-running models at representing the AMOC's strength and meridional heat transport at 35°S and the NBUC volume transport at 11°S.…”
Section: Reanalysis Model Glorys2v4mentioning
confidence: 99%
See 1 more Smart Citation
“…Ocean reanalyses can be studied to enhance understanding of processes driving observed changes. They are also useful for studying recent changes in the climate for quantities that are difficult to observe continuously, such as transports (Mignac et al, 2018), or those that require consistent spatial data coverage at depth, such as ocean heat content (Balmaseda et al, 2013;Wunsch and Heimbach, 2014). To be able to draw robust conclusions, one must be confident that inhomogeneous time series or abrupt regime changes are caused by physically consistent processes -not artifacts associated with changes in the historical observing network.…”
Section: Advances and Unsolved Challenges In Producing Ocean Reanalysesmentioning
confidence: 99%
“…(h) Shows the total northward flow continuing the integration to the western boundary, and is thus a measure of the overturning component of the circulation. FromMignac et al (2017) Mignac et al (2017). showed results for South Atlantic transports in four reanalyses from…”
mentioning
confidence: 99%